Using forest historical information to target landscape ecological restoration in Southwestern Patagonia - Zegers, Gabriel (Ambio, 2019)
Ecotonal zones between eastern semi-arid steppes and Nothofagus spp. forests in western Patagonia are the result of broad ecosystem changes, which have intensified in the last 140 years. Our objectives were to determine historical changes in land use, land cover, and forces driving such changes in Nothofagus ecosystems in the Río Verde district in southern Chile, to support future management recommendations. This interdisciplinary study used historical records including scientific and military expeditions, Landsat imagery, and other archival sources. Forest cover changed radically between the late nineteenth and mid-twentieth centuries, from subsistence use by indigenous peoples, to forestry and livestock industries. The main driving forces of landscape change have been anthropogenic forest fires, logging, exotic pasture establishment, and mining. Future perspectives suggest that conserving the cultural values and natural resources of this region will depend on ecologically sound landscape planning, reversing forest fragmentation, restoring riparian corridors, and preserving indigenous archaeological sites. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13280-019-01232-8) contains supplementary material, which is available to authorized users.